Self Regulated Learning(SRL): Skills in Improving Learning Motivation - Rofi Azmi, Khilman; Arfianti, Kiki (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2021)
The problem that still often occurs in the educational environment is the lack of motivation to learn in students. Each student has a different level of learning motivation, ranging from low, medium, to high learning motivation. The low motivation of students to learn occurs in the lack of a sense of student awareness of the importance of learning motivation. The purpose of this study is to increase learning motivation, using group guidance with self-regulated learning techniques. RS). Self-regulated learning (SRL) is important to be given to students so that students can increase their awareness of their learning motivation. This research is a type of quantitative research with a quasi-experimental research design with an experimental control group design. The results of this study indicate that there are differences before and after the group guidance action with self-regulated learning (SRL) techniques is carried out. So it can be proven that group guidance with self-regulated learning (SRL) techniques can increase the learning motivation of vocational students. SRL can increase students' awareness of learning motivation so that it can be taken into consideration in group guidance services for BK.